Ulva prolifera Polysaccharide–Manganese Alleviates Inflammation and Regulates Microbiota Composition in Dextran Sulfate Sodium-Induced Colitis Mice - Xue, Haoran; Song, Wei; Wang, Zongling; Wang, Qian (Frontiers in Microbiology, 2022)
Manganese (Mn) deficiency exacerbates colitis symptoms, whereas diet supplemented with inorganic Mn merely maintains colon length in experimental colitis. In the present study, a new form of Mn, Ulva prolifera polysaccharide cheated-Mn (PMn) was used and its treatment effects on dextran sulfate sodium (DSS)-induced colitis were investigated. Male C57BL/6 mice were orally administrated with 3.5% DSS to induce colitis. Then, the colitis mice were treated with PBS or PMn for 7 days. The results showed that PMn administration help retrieve the body weight loss and intestinal morphology damage, and alleviate apoptosis and inflammatory responses in colitis mice. Moreover, PMn administration decreased intestinal infiltration as indicated by decreased concentration of myeloperoxidase and eosinophil peroxidase. Importantly, PMn retrieved the increased abundance of Firmicutes and the decreased abundance of Bacteroidetes caused by DSS, suggested its beneficial roles in regulating microbiota composition in mice with colon inflammation. Gut microbiota composition at the genus level in the mice administrated with PMn was similar to those in control mice, whereas they were clearly distinct from DSS-treated mice. These results support the potential therapeutic role of PMn in the treatment of intestinal colitis and microbes may play critical roles in mediating its effects.